PERANCANGAN ULANG ALAT PERAJANG UBI KAYU DENGAN PENDEKATAN ERGONOMI (STUDI KASUS : BUAH TANGAN DUA BUNDA) - Neng Sri Novi Fitri Yani; Ardhan Suhendra (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2015)
Buah Tangan Dua Bunda is home industrial that produced typical food from west sumatera. They produced sanjai chips (cassava chips). Base on the questioner SNQ (Standard Nordic Questioner) toward 3 operators at chopper station shown that the significant muscle problems (MSDs) toward their right hand. The preliminary questioner shown that chopper toll is not good enough, especially for the safety. It can injure operators’ hand. So, in this research, the researcher try to redesign chopper tool to make the operators safety, comfort and reduce the risk of operators’ get muscle problems. The method that using to redesign are developing products, anthropometry, product/ design FMEA and REBA. Developing product method produced planning concept that suitable to the operators, such as; handle, chair (contain of second chair), and planning dimension is gotten by using measurement anthropometry. The chopper tool has width is 79,8 cm and high is 40,3cm. The handle has width is 11,2 cm and high is 57,6 cm. The handful diameter is 40,33 cm. Then chair dimension has width is 43,2 cm, length is 42,8 and high is 40,33 cm. The dimension of portable chair is 35 cm for width and high 23,3 cm. Next , prototype testing with FMEA produced the improvement priority toward the failure method with final result that has safe products and a good performance. The last testing is by using REBA method, prototype can reduce the score form not safety become safety.Keywords: Anthropometry, Developing Product, Product/design FMEA (failure modes and effect analysis), REBA (Rapid Body Assasement), Tool design